UJI PIVOT KLAUSA RELATIF BAHASA MELAYU DELI DAN BAHASA INGGRIS: KAJIAN TIPOLOGI SINTAKSIS - Rizqi, Fahmi Anggia; Mulyadi; Deliana (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Abstract This research aims to explain the Deli Malay and English language pivot system. The data were analyzed using the distribution method with substitution and transformation techniques. The pivot testing was carried out on relative clauses of Deli Malay and English language. The theory which is used is syntactic typology theory. The result of the study showed that Deli Malay and English language is an accusative typology language. The pivot testing shows that Deli Malay and English relative clauses consists of intransitive and transitive clauses with S/A pivot pattern. If the subject (S) in an intransitive clause is treated the same as the agent(A) in a transitive clause but different from the patient (P) in a transitive clause, the language is of the accusative. Keywords: Relative Clause, Accusative, Typology, Pivot